Trends in Active Cigarette Smoking Among Stroke Survivors in the United States, 1999 to 2018. Issue 6 (June 2020) - Parikh, Neal S.; Chatterjee, Abhinaba; Díaz, Iván; Merkler, Alexander E.; Murthy, Santosh B.; Iadecola, Costantino; Navi, Babak B.; Kamel, Hooman
Abstract : Background and Purpose—: Patients who continue to smoke after a stroke face a higher risk of recurrent stroke. While several effective drugs for smoking cessation became available over the past 2 decades, whether active smoking has decreased among stroke survivors is unknown. We, therefore, evaluated trends in active smoking among stroke survivors during this period. Methods—: We performed trends analyses using cross-sectional data collected every 1 to 2 years from 2 US health surveys spanning 1999 to 2018. In the National Health and Nutrition Examination Survey (NHANES) and the Behavioral Risk Factor Surveillance System (BRFSS) survey, participants were asked about prior stroke and active tobacco smoking. In NHANES, serum cotinine levels were available as a secondary measure of active smoking. We used multivariable logistic regression models for survey data to assess trends in active smoking among participants with and without prior stroke. Results—: Among 49 375 participants in NHANES during 1999 to 2016 and 3 621 741 participants in BRFSS during 2011 to 2018, the prevalence of stroke was ≈3%. The overall prevalence of active smoking among stroke survivors was 24% in NHANES and 23% in BRFSS. Among individuals without prior stroke, the odds of smoking decreased over time in both NHANES (odds ratio, 0.95 per 2 years [95% CI, 0.93–0.96]) and BRFSS (odds ratio, 0.96 per year [95% CI, 0.96–0.96]). In contrast, there was no decrease in smoking among stroke survivors in NHANES (odds ratio, 1.00 [95% CI, 0.93–1.07]) or BRFSS (odds ratio, 0.99 [95% CI, 0.98–1.004]). Results were consistent in secondary analysis using biochemical ascertainment of active smoking in NHANES and in sensitivity analyses accounting for potential demographic changes in stroke epidemiology. Conclusions—: In contrast to the general population, the prevalence of active smoking among stroke survivors has not decreased during the past 2 decades.